The relationship of smartphone addiction with depression, obsession-compulsion, impulsivity, alexithymia among medical faculty students - Özen, Seçil; Topcu, Merve (Journal of Dependence, 2017)
Objective: The purpose of current study is to examine the relationship of smartphone addiction (SA) with depression, obsessivecompulsive symptoms (OCS), impulsivity and alexithymia among medical faculty students.Method: A total of 345 medical faculty students who reported smartphone use enrolled in study. Thirty five students who did not fully fill out the questionnaires excluded. Participants completed sociodemographic information form, Smartphone Addiction Scale (SAS), 20-item Toronto Alexithymia Scale (TAS-20), Short Form of Barratt Impulsiveness Scale (BIS-11-SF), and depression and obsessive-compulsive subscales of Symptom Checklist-90 Revised (SCL-90-R) online.Results: As 57.1 % of participants (n=177) are female, 42.9 % of them are male (n=133). Mean of age was 22.40 (SD=±2.40). SA has significantly positive relationship with depression (r=0.351), OCS (r=0.291), difficulty in identifying feelings (r=0.453), impulsivity (r=0.451), difficulty in describing feelings (r=0.860) and alexithymia total (r=0.688). Moreover results of three-stepped Hierarchical regression analysis revealed that depression significantly predicted SA (p
Keywords: Alexithymia; smartphone addiction; depression; impulsivity; obsessive-compulsive symptoms